Fundamentals of the Bioecological Theory of Urie Bronfenbrenner - Collodel Benetti, Idonézia; Vieira, Mauro Luis; Crepaldi, Maria Aparecida; Ribeiro Schneider, Daniela (Pensando Psicología, 2013)
This theoretical research focuses on the following aspects of the Bioecological Theory of Human Development, designed by Urie Bronfenbrenner: a) origins of his proposals, b) ontological bases, c) epistemological bases, d) anthropological point of view, and e) application of the theory - the method and techniques used in research in that particular scientific field. The article was written because of the difficulty of finding scientific writings that address all of these aspects in one single work. It attempts to reveal what is hidden and/or diluted in the scientific discourse underlying the writings of Bronfenbrenner and in a simple and didactic manner to deal with the essential elements needed for a critical understanding of the theory in question.